K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

17 tháng 10 2021

\(25x^2-9=0\)

\(25x^2=9\)

\(x^2=\frac{25}{9}\)

\(x^2=\left(\frac{5}{3}\right)^2=\left(-\frac{5}{3}\right)^2\)

\(\Rightarrow x=\frac{5}{3};x=-\frac{5}{3}\)

17 tháng 10 2021

\(25x^2-9=0\)

\(\Leftrightarrow\)\(25x^2=0+9\)

\(\Leftrightarrow\)\(25x^2=9\)

\(\Leftrightarrow\)\(x^2=\frac{9}{25}\)

\(\Leftrightarrow\)\(x=-\frac{3}{5};\frac{3}{5}\)

9 tháng 11 2018

a) \(x^2-2x=0\)

\(x\left(x-2\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x=0\\x-2=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x=2\end{cases}}}\)

b) \(\left(3x-1\right)^2-16=0\)

\(\left(3x-1\right)^2-4^2=0\)

\(\left(3x-1-4\right)\left(3x-1+4\right)=0\)

\(\left(3x-5\right)\left(3x+3\right)=0\)

\(\Rightarrow\orbr{\begin{cases}3x-5=0\\3x+3=0\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{5}{3}\\x=-1\end{cases}}}\)

c) \(x^2-25x=0\)

\(x\left(x-25\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x=0\\x-25=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x=25\end{cases}}}\)

d) \(\left(4x-1\right)^2-9=0\)

\(\left(4x-1\right)^2-3^2=0\)

\(\left(4x-1-3\right)\left(4x-1+3\right)=0\)

\(\left(4x-4\right)\left(4x+2\right)=0\)

\(\Rightarrow\orbr{\begin{cases}4x-4=0\\4x+2=0\end{cases}\Rightarrow\orbr{\begin{cases}x=1\\x=\frac{-1}{2}\end{cases}}}\)

9 tháng 11 2018

a) \(x^2-2x=0\)

\(x.\left(x-2\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x=0\\x-2=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x=2\end{cases}}}\)

vậy..

b) \(\left(3x-1\right)^2-16=0\)

\(\left(3x-1\right)^2=16\)

\(\left(3x-1\right)^2=4^2=\left(-4\right)^2\)

\(\Rightarrow\orbr{\begin{cases}3x-1=4\\3x-1=-4\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{5}{3}\\x=-1\end{cases}}}\)

vậy ...

c) \(x^2-25x=0\)

\(x.\left(x-25\right)=0\)

\(\Rightarrow\orbr{\begin{cases}x=0\\x-25=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x=25\end{cases}}}\)

vậy ....

d) \(\left(4x-1\right)^2-9=0\)

\(\left(4x-1\right)^2=3^2=\left(-3\right)^2\)

\(\Rightarrow\orbr{\begin{cases}4x-1=3\\4x-1=-3\end{cases}\Rightarrow\orbr{\begin{cases}x=1\\x=\frac{1}{2}\end{cases}}}\)

vậy ...

30 tháng 12 2016

b)   ( 2x - 3 ) - ( 3 - 2x )( x - 1 ) = 0

<=> ( 2x - 3 ) + ( 2x - 3 )( x - 1 ) = 0

<=> ( 2x - 3 )( 1 + x - 1 ) = 0

<=> x( 2x - 3 ) = 0

\(\Leftrightarrow\orbr{\begin{cases}x=0\\2x-3=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\frac{3}{2}\end{cases}}}\)

Vậy .....

30 tháng 12 2016

a, 25x^2 - 1 - (5x -1)(x+2)=0

=> (5x)^2 - 1 + (5x-1)(x+2) = 0

=> (5x-1)(5x+1) + (5x-1)(x+2) = 0

=> (5x-1)(5x+1+x+2) = 0

=> (5x-1)(6x+3) = 0

=> \(\orbr{\begin{cases}5x-1=0\\6x+3=0\end{cases}}\)

24 tháng 8 2024

a)

\(\left(x+2\right)^2-9=0\)

\(\Rightarrow\left(x+2\right)^2=9=3^2\)

\(\Rightarrow x+2=\pm3\)

\(\Rightarrow x=-5;1\)

b)

\(25x^2-10x+1=0\)

\(\left(5x\right)^2-2\cdot5x+1^2=0\)

\(\Rightarrow\left(5x+1\right)^2=0\)

\(\Rightarrow5x+1=0\)

\(\Rightarrow5x=-1;x=\dfrac{-1}{5}\)

c)

\(x^2+14x+49=0\)

\(\Rightarrow x^2+2\cdot7x+7^2=0\)

\(\Rightarrow\left(x+7\right)^2=0;x+7=0\)

\(\Rightarrow x=-7\)

d)

\(\left(2x-1\right)^2+\left(x+3\right)^2-5\left(x+7\right)\left(x-7\right)=0\)

\(4x^2-4x+1+x^2+6x+9-5x^2+5\cdot49=0\)

\(\Rightarrow5x^2-5x^2-4x+6x+10+245=0\)

\(\Rightarrow2x+255=0\)

\(\Rightarrow2x=-255\)

\(\Rightarrow x=\dfrac{-255}{2}\)

 

 

7 tháng 10 2018

Ta có:

\(0.25x^3+x^2+x=0\)

\(\Leftrightarrow x^3+4x^2+4x=0\)

\(\Leftrightarrow x\left(x^2+4x+4\right)=0\)

\(\Leftrightarrow x\left(x+2\right)^2=0\)

\(\Leftrightarrow\orbr{\begin{cases}x=0\\x=-2\end{cases}}\)

7 tháng 10 2018

\(0,25x^3+x^2+x=0\)

\(x\left(0,25x^2+x+1\right)=0\)

\(x\left[\left(0,5x\right)^2+2\cdot0,5x\cdot1+1^2\right]=0\)

\(x\left(0,5x+1\right)^2=0\)

\(\Rightarrow\orbr{\begin{cases}x=0\\0,5x+1=0\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}x=0\\x=-2\end{cases}}\)

Vậy.....

a: \(x^2+12x+36=0\)

\(\Leftrightarrow\left(x+6\right)^2=0\)

\(\Leftrightarrow x+6=0\)

hay x=-6

b: Ta có: \(x^2-1=0\)

\(\Leftrightarrow\left(x-1\right)\left(x+1\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=-1\end{matrix}\right.\)

c: Ta có: \(25x^2-9=0\)

\(\Leftrightarrow\left(5x-3\right)\left(5x+3\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{3}{5}\\x=-\dfrac{3}{5}\end{matrix}\right.\)

AH
Akai Haruma
Giáo viên
11 tháng 9 2021

Lời giải:
a. $x^2+12x+36=0$

$\Leftrightarrow (x+6)^2=0$

$\Leftrightarrow x+6=0$

$\Leftrightarrow x=-6$

b.

$x^2-1=0$

$\Leftrightarrow (x-1)(x+1)=0$
$\Leftrightarrow x-1=0$ hoặc $x+1=0$

$\Leftrightarrow x=1$ hoặc $x=-1$

c. 

$25x^2-9=0$

$\Leftrightarrow (5x)^2-3^2=0$

$\Leftrightarrow (5x-3)(5x+3)=0$

$\Leftrightarrow 5x-3=0$ hoặc $5x+3=0$

$\Leftrightarrow x=\frac{3}{5}$ hoặc $x=-\frac{3}{5}$

10 tháng 7 2018

\(a,25x^2-9=0\)

\(\Leftrightarrow\left(5x-3\right)\left(5x+3\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}5x+3=0\\5x-3=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{3}{5}\\x=\dfrac{3}{5}\end{matrix}\right.\)

\(b,8x^3-50x=0\)

\(\Leftrightarrow2x\left(4x^2-25\right)=0\)

\(\Leftrightarrow2x\left(2x-5\right)\left(2x+5\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=0\\2x-5=0\\2x+5=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=\dfrac{5}{2}\\x=-\dfrac{5}{2}\end{matrix}\right.\)

16 tháng 9 2018

a) \(x^3-25x=0\)

\(\Leftrightarrow x\left(x^2-25\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x^2-25=0\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=\pm5\end{matrix}\right.\)

b) \(4x^2-9-x\left(2x-3\right)=0\)

\(\Leftrightarrow2x^2+3x-9=0\)

\(\Leftrightarrow2x^2-3x+6x-9=0\)

\(\Leftrightarrow x\left(2x-3\right)+3\left(2x-3\right)=0\)

\(\Leftrightarrow\left(2x-3\right)\left(x+3\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}2x-3=0\\x+3=0\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{3}{2}\\x=-3\end{matrix}\right.\)

a) \(25x^2-2=0\)

\(=>\left(5x\right)^2-\left(\sqrt{2}\right)^2=0\)

\(=>\left(5x-\sqrt{2}\right)\left(5x+\sqrt{2}\right)=0\)

\(=>\hept{\begin{cases}5x-\sqrt{2}=0\\5x+\sqrt{2}=0\end{cases}}\)

\(=>\hept{\begin{cases}x=\frac{\sqrt{2}}{5}\\x=-\frac{\sqrt{2}}{5}\end{cases}}\)

b) \(10x-x^2-25=0\)

\(=>-x^2-5x-5x-25=0\)

\(=>-x\left(x+5\right)-5\left(x+5\right)=0\)

\(=>\left(x+5\right)\left(-x-5\right)=0\)

\(=>\hept{\begin{cases}x+5=0\\-x-5=0\end{cases}}\)

\(=>\hept{\begin{cases}x=-5\\x=-5\end{cases}}\)

25 tháng 10 2021

a) \(\left(2x-3\right)\left(2x+3\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{3}{2}\\x=-\dfrac{3}{2}\end{matrix}\right.\)

b) \(x^2-1=0\Rightarrow\left(x-1\right)\left(x+1\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x=1\\x=-1\end{matrix}\right.\)

c) \(x^2-9=0\Rightarrow\left(x-3\right)\left(x+3\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x=3\\x=-3\end{matrix}\right.\)

d) \(\Rightarrow\left(2x-4\right)\left(2x+4\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x=2\\x=-2\end{matrix}\right.\)

2) \(\Rightarrow\left(5x-3\right)\left(5x+3\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{3}{5}\\x=-\dfrac{3}{5}\end{matrix}\right.\)